Non-invasive Vagus Nerve Stimulation in Treatment of Disorders of Consciousness – Longitudinal Case Study - Osińska, Albertyna; Rynkiewicz, Andrzej; Binder, Marek; Komendziński, Tomasz; Borowicz, Anna; Leszczyński, Antoni (Frontiers in Neuroscience, 2022)
Neuromodulatory electroceuticals such as vagus nerve stimulation have been recently gaining traction as potential rehabilitation tools for disorders of consciousness (DoC). We present a longitudinal case study of non-invasive auricular vagus nerve stimulation (taVNS) in a patient diagnosed with chronicunresponsive wakefulness syndrome (previously known as vegetative state). Over a period of six months we applied taVNS daily and regularly evaluated the patient’s behavioural outcomes using Coma Recovery Scale - Revised. We also took electrophysiological measures: resting state EEG and ECG (HR and HRV). All these methods revealed signs of improvement in the patient’s condition. The total CRS-R scores fluctuated but rose from 4 and 6 at initial stages to the heights of 12 and 13 in the 3rd and 5th month, which would warrant a change in diagnosis to a Minimally Conscious State. Scores obtained in a two month follow-up period, though, suggest this may not have been a lasting improvement. Behavioural signs of recovery are triangulated by EEG frequency spectrum profiles with re-emergence of a second oscillatory peak in the alpha range, which has been shown to characterise aware people. However, sustained spontaneous theta oscillations did not predictably diminish, which most likely reflects structural brain damage. ECG measures revealed a steady decrease in pre-stimulation HR combined with an increase in HRV-HR. This suggests a gradual withdrawal of sympathetic and an increase in parasympathetic control of the heart, which the previous literature has also linked with DoC improvements. Together, this study suggests that taVNS stimulation holds promise as a DoC treatment.